Heteropolygonatum binatifolium, a new combination in Heteropolygonatum (Asparagaceae, Polygonateae) - Zhou, Yu-Long; Jiang, Hui; Hu, Guang-Wan; Wang, Qing-Feng (Phytotaxa, 2025)
Through morphological observations and phylogenetic analysis of plastid genomes, Polygonatum binatifolium has been confirmed to belong to the genus Heteropolygonatum, supporting its transfer from Polygonatum to Heteropolygonatum. This taxonomic reassignment establishes it as the thirteenth species in the genus, with the new designation of Heteropolygonatum binatifolium.